2010
DOI: 10.1016/j.crohns.2009.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Anti-colitis and -adhesion effects of daikenchuto via endogenous adrenomedullin enhancement in Crohn's disease mouse model

Abstract: DKT exerts beneficial effects in a CD mouse model through endogenous release and production of ADM. Endogenous ADM may be a therapeutic target for CD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
70
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 77 publications
(77 citation statements)
references
References 38 publications
7
70
0
Order By: Relevance
“…After therapy with daikenchuto, abdominal gas volume assessed by radiographic examination was significantly reduced. Daikenchuto treats abdominal symptoms by enhancing the secretions of motilin (Nagano et al, 1999), substance P (Kono et al, 2008), calcitonin gene-related peptide, and adrenomedullin (Kono et al, 2010(Kono et al, , 2011, and activating the transient receptor potential vanilloid (Kikuchi et al, 2013). Keishikashakuyakuto is also used to treat functional abdominal pain, and the effects on irritable bowel syndrome have been investigated in a double blind RCT (Sasaki et al, 1998).…”
Section: Functional Abdominal Pain or Constipationmentioning
confidence: 99%
“…After therapy with daikenchuto, abdominal gas volume assessed by radiographic examination was significantly reduced. Daikenchuto treats abdominal symptoms by enhancing the secretions of motilin (Nagano et al, 1999), substance P (Kono et al, 2008), calcitonin gene-related peptide, and adrenomedullin (Kono et al, 2010(Kono et al, , 2011, and activating the transient receptor potential vanilloid (Kikuchi et al, 2013). Keishikashakuyakuto is also used to treat functional abdominal pain, and the effects on irritable bowel syndrome have been investigated in a double blind RCT (Sasaki et al, 1998).…”
Section: Functional Abdominal Pain or Constipationmentioning
confidence: 99%
“…In a double-blind, randomized, placebo-controlled study of healthy humans whose gastrointestinal transit and colonic transit were measured by scintigraphy, DKT had a pro-motility effect, especially acceleration of the ascending colon emptying half-time (16). In experimental studies, DKT showed a preventive effect in talc-induced postoperative intestinal adhesion (17,18) and colonic adhesion due to trinitrobenzenesulfonic acid-induced colitis (19). DKT is composed of four medical herbs including zanthoxylum fruit, processed ginger, ginseng, and maltose syrup.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have demonstrated that DKT enhances GI motility both in vitro (7,8) and in vivo (6,9,10), as well as increasing intestinal blood flow (2, 11), reducing the blood ammonia level after hepatectomy (12), and exerting anti-inflammatory effects (13,14). Similarly, recent clinical studies have demonstrated that DKT improves not only GI motility after surgery (15,16) but also attenuates the progression of adhesional bowel obstruction due to abdominal surgery (17,18).…”
Section: Abstract Aim: Although It Has Been Widely Demonstrated Thatmentioning
confidence: 99%
“…However, over the past decade, basic studies using animal models have revealed that the effects of DKT on GI function are mediated by cholinergic and serotonergic nerves (6). Several studies have demonstrated that DKT enhances GI motility both in vitro (7,8) and in vivo (6,9,10), as well as increasing intestinal blood flow (2, 11), reducing the blood ammonia level after hepatectomy (12), and exerting anti-inflammatory effects (13,14).…”
Section: Abstract Aim: Although It Has Been Widely Demonstrated Thatmentioning
confidence: 99%